Occupational Stress in Health Professionals of Combined Military Hospitals (Journal of Armed Forces Medical College, Bangladesh, 2017)
Introduction: Stress is a term that is widely used in everyday life. Work-related stress is recognized globally as a major challenge to workers’ health and the health of an organization. Stress at work has become a serious problem affecting many people of different professions, life situation and age groups. The healthcare profession has been depicted as one of the most stressful occupations across the globe.Objective: To assess the extent of occupational stress among health professionals of Combined Military Hospitals and to explore its association with work-related factors and family-work interference.Materials and Methods: A total of 574 respondents were selected from five Combined Military Hospitals using simple random sampling considering doctors, nurses, paramedic medical assistants and technologists as the study population. Occupational stress was determined by Health Professions Stress Inventory (HPSI).Results: Stress of health professionals was reassessed through HPSI and 1.0%, 77.6%, 20.7% and 0.8% were found to be mild, moderate, very and extremely stressful respectively. About one fifth (21.4%) were found to be in high stress. High stress was more prevalent among Paramedic Medical Assistants (PMAs) (24.5%), Paramedic Medical Technologists (PMTs) (23.2%) and nurses (21.9%) on contrary to doctors (11.7%). Their mean stress scores were 55.70±13.75, 55.44±13.53, 56.18±10.55 and 50.92±10.93 respectively (p